Cooperative learning: improving students' understanding, social skills, and motivation - Ahmad Alwi; Athifa Radella tabina; Nurul Azmi Aziz (Lenggogeni Data Publishing, 2024)
The research used by researchers here is in the form of descriptive research using a qualitative approach. Descriptive means research that attempts to observe problems systematically and accurately regarding certain facts and objects. Descriptive research aims to explain, describe and map facts based on a certain perspective or way of thinking. The way to collect data from this research is by using observation research, interviews and documentation. The research results show that cooperative learning is really needed. So based on observations, interviews and documentation, cooperative learning activities are held through existing learning activities at school. This is very influential for today's students, so that students learn through interaction with their group members, sharing ideas, solving problems together, and providing feedback to each other. Cooperative learning has several benefits. First, it increases students' understanding because they can explain concepts to each other and help each other understand the material.